Aerodynamic performance analysis of corrugated dragonfly-wing airfoil for small wind turbine blade application - Naval, Christopher T.; Luzon, Roque R.; Leung, Yownin Albert M.; Maglasang, Jonathan C.
A biomimetic design was investigated to enhance the performance of small horizontal axis wind turbine. The aerodynamic performance of a corrugated dragonfly-wing airfoil was evaluated using wind tunnel experimentations and CFD simulations. At Reynolds number of 40000 to 370000, the corrugated dragonfly-wing blade had the highest lift coefficient and lift to drag ratio among the airfoils tested. It was evident that at high angles of attack, the corrugated dragonfly wing blade exhibited the best aerodynamic performance because of its unique capability of delaying the onset of flow separation due to the effects of corrugation. A better wind turbine design was achieved because of the high lift generated and the added structural integrity to the rotor blades provided by the corrugated configurations of the dragonfly-wing airfoil.
Keywords: Dragonfly-wing.; Wind turbine; Wind tunnel experimentation; Computational fluid dynamics